STRATEGI PEMERINTAH TERHADAP PENINGKATAN KESEJAHTERAAN MASYARAKAT DI DESA PATTONDONSALU KABUPATEN ENREKANG - Surahman Al Fajar; Haeruddin Syarifuddin; Muhammad Rais Rahmat Razak (LPPM Universitas Abdurrab, 2025)
The El Niño phenomenon, which caused prolonged drought, has had a serious impact on community food security, particularly in rural areas such as Pattondonsalu Village, Enrekang Regency. The government responded to this situation through the Government Food Reserve Program (CPP), providing rice assistance to affected communities. However, the program's effectiveness in improving community welfare remains questionable. This study aims to evaluate the effectiveness of CPP rice assistance and identify more appropriate government strategies for improving community welfare.This study used a quantitative approach with descriptive methods. Data were collected through questionnaires distributed to CPP recipients in Pattondonsalu Village. Data analysis was conducted using SPSS, using validity and reliability tests, and simple regression analysis.The results showed that the CPP rice assistance program only contributed 2.5% to community welfare improvement, with 97.5% being influenced by factors other than the assistance itself. This finding indicates that although the rice assistance was welcomed, it did not fully address the needs of the community, most of whom already had rice reserves from their own harvests.In conclusion, the government's strategy of CPP rice assistance was deemed ineffective in the context of Pattondonsalu Village. Therefore, a more contextual and local-oriented approach is needed, such as providing agricultural production facilities, training, and market access, to support community welfare in a sustainable manner.